EPR characterization of erbium in glasses and glass ceramics - Antuzevics, Andris (AIP Publishing, 2020)
Electron paramagnetic resonance (EPR) is a well-established spectroscopic technique for electronic structure characterization of rare-earth ion impurities in crystalline and amorphous hosts. EPR spectra of erbium-doped glass matrices and nanocomposites can provide information about local structure variations induced by changes in chemical composition or crystallization processes. Characterization possibilities of Er3+ ions in glasses and glass ceramics including direct EPR measurements, indirect investigations via secondary paramagnetic probes, and optically detected magnetic resonance techniques are considered in this article. ----/ / /---- This is the pre-print of the following article: A. Antuzevics, EPR characterization of erbium in glasses and glass ceramics, Low Temperature Physics 46, 1149 (2020), which has been published at https://aip.scitation.org/doi/10.1063/10.0002465 under license by AIP Publishing. This article may be used for non-commercial purposes in accordance with AIP Publishing Terms and Conditions for Sharing and Self-Archiving.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; electron paramagnetic resonance (EPR); erbium; oxyfluoride; glass; glass ceramics